Protective effects of ascorbic acid pretreatment in a rat model of intestinal ischemia-reperfusion injury: a histomorphometric study (Clinics, 2007)
BACKGROUND: Ascorbic acid has shown promise in attenuation of intestinal ischemia-reperfusion (I/R) injury. The aim of this study was to determine the protective effects of ascorbic acid on intestinal morphology during IR injury in rats. MATERIALS AND METHODS: We examined morphological changes in the small intestine of Wistar rats after (i) 40 minutes of ischemia (I), (ii) ischemia followed by 30 min of reperfusion (IR), (iii) ischemia with ascorbic acid (IA), (iv) ischemia followed by reperfusion and ascorbic acid (IRA) and (v) in a sham group (S). We used morphometry to evaluate the amount of villous architecture, crypts, necrosis, hemorrhagic infarcts and inflammatory cells at the mesenteric and antimesenteric borders of the small intestine. RESULTS: Ascorbic acid caused a significant reduction of antimesenteric villous hemorrhagic infarction (p